A Notação Íntima do Sentimento Brasileiro em Minha Formação, de Joaquim Nabuco - Fábio Nascimento Sandes (Porto das Letras, 2016)
Firstly we will examine how the idea of writing an autobiography appeared in Nabuco, and then how the Brazilian feeling sets upon his formation. At the age of 50, Nabuco thought that he had already given to much of himself to others, and had the right, compared to the experiences in Brazil and abroad, to give a little to himself, by not only cutting edges in his intimate way, but writing his history of life and formation of his country. Secondly, we will reflect upon his biography based on two themes: art and nature, in order to better understand the extent in which the “self-fabrication” is guided by natural principles and the artificiality of culture. This ambiguity is spread all over Minha Formação, especially when he states that “our imagination cannot be other than European”, as he will later convey: “in America it lacks the historical background and the human perspective to landscape, life, the horizon, architecture, everything that surrounds us, and in Europe we lack the homeland, that is, the way each one of us was cast at birth”. It should be noted that the narrator of these sections is a Nabuco, but in his young period of life, filled with feelings of instability, curiosity, and indecision. Our purpose herein was to identify how the author has criticized his early years and in what degree he has combined his Brazilian and foreign private notes to converge the process of maturation of a Brazilian writer divided into the artifice of European culture and the intimate heart of a Brazilian.